SUFISME JAWA DALAM SERAT SASTRA GENDING SULTAN AGUNG MATARAM - Muhammad Ilham Aziz; Dudung Abdurrahman (Aqlam: Journal of Islam and Plurality, 2022)
Abstract: This article discusses Sufism in the Serat Sastra Gending Sultan Agung which had an influence on Javanese literature in Mataram. Sultan Agung Sufism teaching based on this fiber describe a kings desire to convery the teachings of Islam, especially Sufisme patterned Islam to his people through a Javanese cultural approach. Therefore, it is identified through this study as “Javanese Sufism”. The main problem of this research how is the Javanese Sufism pattern reflected in Sultan Agung view? and why did Sultan Agung Sufism teaching influence Javanese literature in the Mataram area? This study was developed using the history of thought method. The findings of this study are as follows: First, the socio-religious conditions at the time of Sultan Agung wereclosely related to the pantheism that was embraced by the Javanese inland community. Second, the teachings of Sultan Agung Sufism in the serat sastra Gending show two things that are interrelated and need, which are reflected in the relationship between man and God (the creator). The concept of Sufism in describes the acculturation of three cultures: Javanese, Hindu, and Islamic. Third, the teaching of Sultan Agung Sufism are included in the syncretic teachings influenced the development of Javanese literature in Mataram. The urgency of Sufism teachings framed in the form of literature is able to explain religion and political polices until the next period after Sultan Agung.  Keyword: King’s View, Sastra Gending, Javanese Sufism. Abstrak: Artikel ini membahas sufisme dalam Serat Sastra Gending Sultan Agung yang memberi pengaruh terhadap kesusastraan Jawa di Mataram.  Ajaran tasawuf Sultan Agung ini berdasarkan serat ini menggambarkan suatu keinginan seorang raja untuk menyampaikan ajaran agama Islam, khususnya Islam bercorak tasawuf kepada rakyatnya melalui pendekatan budaya Jawa. Karena itu, teridentifikasi melalui kajian ini sebagai "Sufisme Jawa".  Pokok masalah penelitian ini adalah bagaimana corak sufisme-Jawa tercermin dari pandangan Sultan Agung? dan mengapa ajaran tasawuf Sultan Agung berpengaruh terhadap kesusastraan Jawa di wilayah Mataram?. Studi ini dikembangkan dengan metode sejarah pemikiran. Adapun temuan kajian ini sebagai berikut: Pertama, kondisi sosial keagamaan pada masa Sultan Agung lekat dengan panteisme yang dianut oleh masyarakat Jawa pedalaman. Kedua, ajaran tasawuf Sultan Agung dalam Serat Sastra Gending memperlihatkan dua hal yang saling berkaitan dan membutuhkan, yang tergambar dalam hubungan manusia dengan Tuhan (pencipta). Adapun konsep tasawuf di dalamnya menggambarkan akulturasi tiga budaya: Jawa, Hindu, dan Islam. Ketiga, ajaran tasawuf Sultan Agung termasuk dalam ajaran tasawuf yang sinkretis. Ajaran tersebut berpengaruh terhadap perkembangan kesusastraan Jawa di Mataram. Urgensi ajaran tasawuf yang dibingkai dalam bentuk sastra mampu menjelaskan agama dan kebijakan politik hingga masa selanjutnya pasca Sultan Agung. Kata Kunci : Pandangan Raja, Sastra Gending, Sufisme Jawa.